1981
DOI: 10.1002/prac.19813230514
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins. LXXXIII. Molecular and crystal structure of “Hydrogeno I”, a hydrogenolysis product of gibberellin A3 methyl ester

Abstract: Gibberellins. LXXXIII. Molekül‐ und Kristallstruktur von „Hydrogeno I”︁, einem Hydrierprodukt von Gibberellin‐A3‐methylester Im Zusammenhang mit stereochemischen Untersuchungen an Gibberellinverbindungen wurde die Molekül‐ und Kristallstruktur von „Hydrogeno I”︁ 2, einem Produkt der katalytischen Hydrierung von Gibberellin‐A3‐methylester, durch Röntgenstrukturanalyse bestimmt. Verbindung 2 kristallisiert in der orthorhombischen Raumgruppe P212121 mit den Gitterkonstanten a = 10,316, b = 17,214 und c = 10,341 Å… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…An X-ray analysis of the hydrogenolysis acid, 'hydrogeno-1 ' (14), revealed that it retained a P-proton at C-9. 34 The products of relactonization of the hydrogenolysis acids possess the same C-5 and C-9 stereochemistry as the parent gibberellic acid. Oxidation of methyl gibberellate with manganese dioxide affords the ap-unsaturated ketone (24).…”
Section: The Stereochemistry Of Reductionmentioning
confidence: 98%
See 1 more Smart Citation
“…An X-ray analysis of the hydrogenolysis acid, 'hydrogeno-1 ' (14), revealed that it retained a P-proton at C-9. 34 The products of relactonization of the hydrogenolysis acids possess the same C-5 and C-9 stereochemistry as the parent gibberellic acid. Oxidation of methyl gibberellate with manganese dioxide affords the ap-unsaturated ketone (24).…”
Section: The Stereochemistry Of Reductionmentioning
confidence: 98%
“…Methanol also adds across the double bond and in the presence of sodium methoxide a retro-Claisen reaction occurs with the formation of the adduct (33). 54 The stereochemistry of these adducts and their reduction products have been established by X-ray cry~tallography.~~ The addition of azide ion across the double bond to form the la-and Ip-azides (34) occurs56 readily and also provides a route to the l-hydroxygibberellins. Reduction of the 3-ketones gave the corresponding azido-alcohols which were photolysed to form the imines and thence the 1-ketones from which gibberellins A,, (35) and A,, (36) were prepared.…”
Section: Conjugate Addition To the Al-3-ketogibberellinsmentioning
confidence: 99%
“…None, however, exhibited a C9--C15 bond as observed in (2) and only two had a C1--C10 double bond: 2,7-dihydroxy-10-methoxycarbonyl-l-methyl-8-methylene-4/3-gibberell-4-ene-1-carboxylic acid (Kutschabsky, Reck, Adam, Argay & Czugler, 1981) and ent-3a, 13 -dihydroxy-7-methoxycarbonyl-20-norgibberella-l(10),16-diene-19-carboxylic acid (Kutschabsky, Adam & Voigt, 1987).…”
mentioning
confidence: 98%